Baicalin alleviates chronic obstructive pulmonary disease through regulation of HSP72-mediated JNK pathway - Dexun Hao; Yanshuang Li; Jiang Shi; Junguang Jiang (BMC, 2021)
Abstract Background Chronic obstructive pulmonary disease (COPD) is characterized by airway obstruction and progressive lung inflammation. As the primary ingredient of a traditional Chinese medical herb, Baicalin has been previously shown to possess anti-inflammatory abilities. Thus, the current study aimed to elucidate the mechanism by which baicalin alleviates COPD. Methods Baicalin was adopted to treat cigarette smoke in extract-exposed MLE-12 cells after which cell viability and apoptosis were determined. The production of tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6), IL-8 were determined by enzyme-linked immunoassay. A COPD mouse model was constructed via exposure to cigarette smoke and lipopolysaccharide, baicalin treatment. Lung function and inflammatory cell infiltration were determined and the production of Muc5AC, TNF-α, IL-6, IL-8 in the bronchoalveolar lavage fluid (BALF) was assayed by ELISA. The effect of HSP72 and JNK on COPD following treatment with baicalin was assessed both in vivo and in vitro by conducting loss- and gain- function experiments. Results Baicalin improved lung function evidenced by reduction in inflammatory cell infiltration and Muc5AC, TNF-α, IL-6 and IL-8 levels observed in BALF in mice. Baicalin was further observed to elevate cell viability while inhibited apoptosis and TNF-α, IL-6 and IL-8 levels in MLE-12 cells. Baicalin treatment increased HSP72 expression, while its depletion reversed the effect of baicalin on COPD. HSP72 inhibited the activation of JNK, while JNK activation was found to inhibit the effect of baicalin on COPD. Conclusions Baicalin upregulated the expression of HSP72, resulting in the inhibition of JNK signaling activation, which ultimately alleviates COPD.